PEMBENTUKAN KEYAKINAN HAKIM DALAM PERKARA PIDANA DI LINGKUNGAN PERADILAN JAWA BARAT - Ijud Tajudin; Rully Herdita Ramadhani; Azadia Az Zahra (Arena Hukum, 2020)
AbstractIt is interesting to examine how a judge can convince himself that he has found the material truth of a criminal act. The purpose of this study is to find the measurement and criteria of judges' confidence in the evidentiary process of a trial in finding material truth in the judiciary of West Java Province and the factors influenced the formation of the judge's conviction in deciding criminal cases. This normative study is analyzed using qualitative data. The results show that the establishment of judges' beliefs in criminal cases in the judiciary of West Java Province is based on the evidence according to what is regulated in Article 184 (1) of the Criminal Procedure Code and the facts at the hearing. The formation of the judge's conviction is seen from whether there is a match between the statements of the witnesses, the statements of witnesseses with other evidence and with the statements of the defendant related to the case charged by the Public Prosecutor. If the facts are found that are the result of conformity between the witness testimony and other evidence and the defendant's statement with the elements of the article charged, then the judge's conviction emerges / is formed. Some factors that influence judges in forming beliefs include experience of the judges, the form of a single judge and panel of judges, Court Class (I A or I B), and cultural and religious background. AbstrakMenarik untuk diteliti mengenai bagaimana seorang hakim dapat meyakinkan dirinya sendiri bahwa ia telah menemukan kebenaran materiil dari suatu tindak pidana. Tujuan penelitian ini adalah untuk menemukan ukuran dan kriteria keyakinan hakim terhadap proses pembuktian di persidangan dalam menemukan kebenaran materiil pada lembaga peradilan di wilayah hukum Provinsi Jawa Barat dan faktor-faktor apakah yang mempengaruhi pembentukan keyakinan hakim dalam memutus perkara pidana. Penelitian normative ini dianalisis dengan data kualitatif. Hasil menunjukkan bahwa Pembentukan keyakinan hakim dalam perkara pidana pada lembaga peradilan di wilayah hukum Provinsi Jawa Barat didasarkan pada alat bukti sesuai dengan yang diatur di dalam Pasal 184 ayat (1) KUHAP dan fakta-fakta di persidangan. Terbentuknya keyakinan hakim dilihat dari apakah ada kesesuaian antara keterangan para saksi, keterangan antara para saksi dengan alat bukti lain dan dengan keterangan terdakwa terkait perkara yang didakwakan oleh Jaksa penuntut Umum. Apabila ditemukan fakta-fakta yang merupakan hasil kesesuaian antara keterangan para saksi dengan alat bukti lain dan keterangan terdakwa dengan unsur-unsur pasal yang didakwakan, maka keyakinan hakim muncul/terbentuk. Beberapa faktor yang mempengaruhi hakim dalam pembentukan keyakinan antara lain pengalaman/jam terbang hakim, bentuk hakim tunggal dan hakim majelis, Kelas Pengadilan (I A atau I B), dan latar belakang budaya dan Agama.